Non-aqueous electrolyte and lithium ion battery

By adding specific compounds as the first additive to the nonaqueous electrolyte of the lithium-ion battery and using sulfate/sulfonate or phosphate compounds as the second additives, an optimized SEI film is formed, which solves the shortcomings of the lithium-ion battery in high-temperature storage and high-temperature cycling performance, and achieves the efficient and safe high-temperature performance of the battery.

CN119812475APending Publication Date: 2025-04-11SHENZHEN CAPCHEM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510087474.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-04-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing lithium-ion batteries containing unsaturated phosphate or sulfate/sulfonate cannot meet market demand in terms of high-temperature storage and high-temperature cycling performance.

Method used

A nonaqueous electrolyte solution is used, comprising a solvent, an electrolyte salt, a first additive and a second additive, wherein the first additive is selected from a specific compound and the second additive is selected from a sulfate/sulfonate or a phosphate compound. The nonaqueous electrolyte is preferentially formed on the negative electrode during the battery formation process, which suppresses the side reaction between the electrolyte and the negative electrode, and decomposes on the surface of the positive electrode to stabilize the structure of the positive electrode material, thereby improving the high-temperature circulation and high-temperature storage performance of the battery.

Benefits of technology

It significantly improves the high-temperature cycling and high-temperature storage performance of lithium-ion batteries, ensuring the stability and safety of the battery under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

In order to solve the problem that an existing battery is insufficient in high-temperature storage and high-temperature cycle performance, the invention provides a non-aqueous electrolyte which comprises a solvent, an electrolyte salt, a first additive and a second additive, the first additive is selected from at least one of compounds shown in a structural formula 1: A-D-B-E-C structural formula 1, a, B and C are independently selected from a group containing a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfonyl group, a cyclic sulfoxide group, a cyclic carboxylate group or a cyclic anhydride group; d and E are independently selected from single bonds or groups containing alkylene, ether bonds, sulfur-oxygen double bonds or carbon-oxygen double bonds; and the second additive is selected from at least one of a sulfate / sulfonate compound as shown in a structural formula 2 and a phosphate compound as shown in a structural formula 3. The electrolyte can effectively improve the high-temperature storage and high-temperature cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a non-aqueous electrolyte and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in daily life and production due to their excellent performance. In recent years, with the development of consumer electronics and new energy vehicles, the battery industry has increasingly demanded high energy density of lithium-ion batteries.

[0003] The design of high energy density lithium-ion batteries can be started from the following aspects: 1. Increase the gram capacity of the positive electrode material; 2. Increase the battery discharge platform; 3. Increase the proportion of active materials in the battery, etc. Increasing the charging cut-off voltage of lithium-ion batteries is one of the important ways to increase the battery energy density, because with the increase of the charging cut-off voltage, the positive electrode material can achieve a higher gram capacity, and the discharge platform is significantly improved. The two aspects have an immediate effect on the improvement of energy density.

[0004] As the battery voltage gradually increases, the positive electrode material enters a higher delithiation state, the material structure stability will deteriorate, and the surface oxidation will also increase significantly. With the development of high-gram capacity positive electrode materials, the instability of the material structure and its high oxidation are particularly evident at the electrode / electrolyte interface, which is specifically manifested as: battery gas production, rapid increase in internal resistance, and a sharp drop in capacity. Battery gas production will lead to increased internal pressure, which may further develop into dangerous situations such as battery explosion and combustion.

[0005] In order to improve these problems, protecting battery materials is one of the important means. For example, by adding a small amount of unsaturated phosphate or sulfate / sulfonate additives to the electrolyte, a stable protective film can be formed on the positive electrode surface to avoid side reactions between the electrolyte and the positive electrode material, effectively controlling the battery's gas production, rapid increase in internal resistance, and sharp decrease in capacity. However, a large number of studies have found that although unsaturated phosphate or sulfate / sulfonate additives can control battery gas production, internal resistance growth, and capacity decrease, they still cannot meet market needs in terms of high-temperature storage and high-temperature cycle performance, and further improvements are needed in the high-temperature storage and high-temperature cycle performance of batteries. Summary of the invention

[0006] The technical problem solved by the present invention is that the high-temperature storage and high-temperature cycle performance of existing lithium-ion batteries containing unsaturated phosphates or sulfates / sulfonates cannot meet market needs, thereby providing a non-aqueous electrolyte and lithium-ion battery with good high-temperature cycle performance and high-temperature storage performance.

[0007] The purpose of the present invention is achieved through the following technical solutions: In one aspect, the present invention provides a non-aqueous electrolyte, comprising a solvent, an electrolyte salt, a first additive and a second additive, wherein the first additive is selected from at least one of the compounds shown in Structural Formula 1: ADBEC Structural formula 1 wherein A, B, and C are each independently selected from a group containing a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group; D and E are each independently selected from a single bond, or a group containing an alkylene group, an ether bond, a sulfur-oxygen double bond, or a carbon-oxygen double bond; The second additive is selected from at least one of a sulfate / sulfonate compound as shown in Structural Formula 2 and a phosphate compound as shown in Structural Formula 3: Structural formula 2 Among them, R 14 is selected from oxygen, F-containing C1-C5 alkylene, C1-C5 saturated alkylene or unsaturated alkylene, R 15 is selected from a hydrogen atom, a halogen atom or a C1-C5 alkyl group, and n is selected from an integer of 0 to 3; Structural formula 3 Among them, R 16 , R 17 , R 18 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group or a halogenated hydrocarbon group, and R 16 , R 17 , R 18 At least one of them is an unsaturated hydrocarbon group; Based on the total mass of the non-aqueous electrolyte as 100%, the amount of the first additive added is 0.01-5.0%; The addition amount of the sulfate / sulfonate compound represented by the structural formula 2 is 0.01-5.0%; The added amount of the phosphate compound represented by the structural formula 3 is 0.01-1.0%.

[0008] Optionally, the number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups and cyclic anhydride groups independently contained in A, B and C is 1 to 5, and the total number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups and cyclic anhydride groups contained in A, B and C is less than or equal to 10.

[0009] Optionally, A and C are each independently selected from the group shown in structural formula 4: Structural formula 4 wherein n is an integer selected from 0 to 4, R1 is selected from hydrogen, halogen, C1 to C5 hydrocarbon group or halogenated hydrocarbon group; R2, R3, R4, R5, R6, and R7 are each independently selected from C1 to C3 hydrocarbon group, C1 to C3 alkoxy group, oxygen atom, , or , at least one of R2, R3, and R4 is selected from , or , and at least one of R2, R3, and R4 is selected from an oxygen atom, and at least one of R5, R6, and R7 is selected from , or , and at least one of R5, R6, and R7 is selected from an oxygen atom.

[0010] Optionally, B is selected from the group shown in structural formula 5: Structural formula 5 Wherein, m is selected from an integer of 1 to 4, R8, R9, R 10 Each independently selected from a C1-C3 alkylene group, a C1-C3 alkoxy group, an oxygen atom, , or , R8, R9, R 10 At least one selected from , or , and R8, R9, R 10 At least one of them is selected from oxygen atoms.

[0011] Optionally, D and E are each independently selected from the group shown in structural formula 6: Structural formula 6 Wherein, z is selected from an integer of 0 to 4, R 11 and R 13 Each independently selected from a single bond or a C1-C5 alkylene group, R 12 Selected from single bonds, , , , , , , , , or .

[0012] Optionally, D and E are each independently selected from a single bond or a C1-C5 alkylene group, and A, B, and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group; Preferably, when A, B or C is substituted, the substituent is selected from halogen, hydrocarbon group or halogenated hydrocarbon group. More preferably, when A, B or C is substituted, the substituent is selected from halogen, alkyl group or halogenated alkyl group.

[0013] Optionally, A and C are the same as each other, A and B are the same as or different from each other, and D and E are the same as each other.

[0014] Optionally, the sulfate / sulfonate compound represented by Structural Formula 2 is selected from at least one of the following compounds: ; The phosphate compound represented by structural formula 3 is selected from at least one of the following compounds: .

[0015] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the amount of the first additive added is denoted as x, and the amount of the sulfate / sulfonate compound shown in the structural formula 2 is denoted as y, and these substances satisfy the following relationship: 1%<y≤5%, and 0.01%≤x≤1%; Or 0.01%≤y≤1%, and 1%<x≤5%.

[0016] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the amount of the first additive added is x, and the amount of the phosphate compound shown in the structural formula 3 added is z, and these substances satisfy the following relationship: 0.1%<x+z<2%; Furthermore, preferably, 0.1%<x<2%, 0.01%<z<0.5%, and 0.1%<x+z<2%.

[0017] On the other hand, the present invention further provides a lithium ion battery comprising a positive electrode, a negative electrode and the non-aqueous electrolyte as described above.

[0018] According to the non-aqueous electrolyte provided by the present invention, the compound shown in structural formula 1 is added to the electrolyte, and at the same time, the sulfate / sulfonate compound shown in structural formula 2 or the phosphate compound shown in structural formula 3 is used. During the battery formation process, the inventor speculates that the additive of structural formula 1 forms an SEI film at the negative electrode before the sulfate / sulfonate compound shown in structural formula 2 or the phosphate compound shown in structural formula 3, passivates the surface of the negative electrode, thereby inhibiting the consumption of the sulfate / sulfonate shown in structural formula 2 or the phosphate shown in structural formula 3 at the negative electrode, avoiding side reactions between the electrolyte and the negative electrode, and at the same time allowing the sulfate / sulfonate or phosphate compound to decompose more on the positive electrode surface, stabilizing the structure of the positive electrode material, and inhibiting the dissolution of metal ions under high voltage, thereby achieving stable performance during high-temperature cycling and high-temperature storage. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0020] An embodiment of the present invention provides a non-aqueous electrolyte, including a solvent, an electrolyte salt, a first additive and a second additive, wherein the first additive is selected from at least one of the compounds shown in Structural Formula 1: ADBEC Structural formula 1 wherein A, B, and C are each independently selected from a group containing a cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group; D and E are each independently selected from a single bond, or a group containing an alkylene group, an ether bond, a sulfur-oxygen double bond, or a carbon-oxygen double bond; The second additive is selected from at least one of a sulfate / sulfonate compound as shown in Structural Formula 2 and a phosphate compound as shown in Structural Formula 3: Structural formula 2 Among them, R 14 is selected from oxygen, F-containing C1-C5 alkylene, C1-C5 saturated alkylene or unsaturated alkylene, R 15 is selected from a hydrogen atom, a halogen atom or a C1-C5 alkyl group, and n is selected from an integer of 0 to 3; Structural formula 3 Among them, R 16 , R 17 , R 18Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group or a halogenated hydrocarbon group, and R 16 , R 17 , R 18 At least one of them is an unsaturated hydrocarbon group; Based on the total mass of the non-aqueous electrolyte being 100%, the amount of the first additive added is 0.01-5.0%; the amount of the sulfate / sulfonate compound represented by the structural formula 2 added is 0.01-5.0%; The added amount of the phosphate compound represented by the structural formula 3 is 0.01-1.0%.

[0021] According to the non-aqueous electrolyte provided by the present invention, the compound shown in structural formula 1 is added to the electrolyte, and the sulfate / sulfonate compound shown in structural formula 2 or the phosphate compound shown in structural formula 3 is used at the same time. During the battery formation process, the inventor speculates that the additive of structural formula 1 forms an SEI film at the negative electrode before the sulfate / sulfonate compound shown in structural formula 2 or the phosphate compound shown in structural formula 3, passivates the surface of the negative electrode, thereby inhibiting the consumption of the sulfate / sulfonate compound shown in structural formula 2 or the phosphate compound shown in structural formula 3 at the negative electrode, avoids side reactions between the electrolyte and the negative electrode, and at the same time makes the sulfate / sulfonate compound shown in structural formula 2 or the phosphate compound shown in structural formula 3 decompose more on the positive electrode surface, stabilizes the structure of the positive electrode material, and inhibits the dissolution of metal ions under high voltage, thereby achieving stable performance during high-temperature cycling and high-temperature storage.

[0022] The inventors have found that when the amount of the sulfate / sulfonate compound shown in Structural Formula 2 is 0.01-5.0%, 0.01-5.0% of the first additive shown in Structural Formula 1 is added to the non-aqueous electrolyte. The inventors speculate that during the battery formation process, the additive of Structural Formula 1 is reduced before the sulfate / sulfonate compound shown in Structural Formula 2, forming an inner SEI on the surface of the negative electrode, and then the sulfate / sulfonate compound shown in Structural Formula 2 is reduced to form an outer SEI, and the decomposition products of the two include sulfur-containing organic matter and inorganic matter. The short-chain organic product reduced by the sulfate / sulfonate compound shown in Structural Formula 2 and the product of the inner layer of Structural Formula 1 will polymerize under the catalysis of a specific substance to generate a long-short ABA long-chain product, and the inner and outer layers together form a more optimized SEI, which is conducive to ion transport and avoids side reactions between the electrolyte and the negative electrode. At the same time, the compound of structural formula 1 significantly inhibits the consumption of the sulfate / sulfonate compound shown in structural formula 2, so that the sulfate / sulfonate compound shown in structural formula 2 is more decomposed on the positive electrode surface, stabilizes the structure of the positive electrode material, and inhibits the dissolution of metal ions under high voltage, thereby achieving stable performance during high-temperature cycling and high-temperature storage.

[0023] Similarly, by adding 0.01% to 1.0% of the unsaturated phosphate compound shown in formula 3 to the electrolyte, a passivation film can be formed at the positive electrode by reacting, and the passivation film isolates the electrolyte from the high-voltage positive electrode interface, thereby inhibiting the side reaction at the electrolyte and positive electrode interface. However, since the LUMO energy level of the compound phosphate shown in formula 3 is low, it is easy to form a film on the surface of the negative electrode, significantly increasing the negative electrode impedance. The inventors have found that on this basis, adding 0.01 to 5.0% of the first additive shown in formula 1, it is speculated that the compound of structure 1 can form SEI at the negative electrode in priority to the phosphate compound shown in formula 3, passivate the negative electrode surface, thereby inhibiting the consumption of the compound phosphate shown in formula 3 at the negative electrode, and making it react more at the positive electrode, which not only better protects the positive electrode, but also improves the high-temperature storage and high-temperature cycle performance of the battery.

[0024] In some embodiments, the number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups and cyclic anhydride groups independently contained in A, B, and C is 1 to 5, and the total number of cyclic carbonate groups, cyclic sulfate groups, cyclic sulfite groups, cyclic sulfonate groups, cyclic sulfone groups, cyclic sulfoxide groups, cyclic carboxylate groups and cyclic anhydride groups of A, B, and C is less than or equal to 10.

[0025] In some embodiments, A and C are each independently selected from the group shown in Structural Formula 4: Structural formula 4 wherein n is an integer selected from 0 to 4, R1 is selected from hydrogen, halogen, C1 to C5 hydrocarbon group or halogenated hydrocarbon group; R2, R3, R4, R5, R6, and R7 are each independently selected from C1 to C3 hydrocarbon group, C1 to C3 alkoxy group, oxygen atom, , or , at least one of R2, R3, and R4 is selected from , or , and at least one of R2, R3, and R4 is selected from an oxygen atom, and at least one of R5, R6, and R7 is selected from , or , and at least one of R5, R6, and R7 is selected from an oxygen atom.

[0026] In a preferred embodiment, the combination of -R3-R2-R4- and the combination of -R7-R5-R6- are each independently selected from , , , , , or .

[0027] In some embodiments, B is selected from the group shown in Structural Formula 5: Structural formula 5 Wherein, m is selected from an integer of 1 to 4, R8, R9, R 10 Each independently selected from a C1-C3 alkylene group, a C1-C3 alkoxy group, an oxygen atom, , or , R8, R9, R 10 At least one selected from , or , and R8, R9, R 10 At least one of them is selected from oxygen atoms.

[0028] In a preferred embodiment, -R9-R8-R 10 -The combination groups are each independently selected from , , , , , or .

[0029] In some embodiments, D and E are each independently selected from the group shown in Structural Formula 6: Structural formula 6 Wherein, z is selected from an integer of 0 to 4, R 11 and R 13 Each independently selected from a single bond or a C1-C5 alkylene group, R 12 Selected from single bonds, , , , , , , , , or .

[0030] In some embodiments, A and C are the same as each other, A and B are the same as or different from each other, and D and E are the same as each other.

[0031] When A and C are the same as each other, and D and E are the same as each other, the compound shown in Structural Formula 1 is a symmetrical structure. Compared with an asymmetrical structure, the compound shown in Structural Formula 1 with a symmetrical structure is easier to synthesize, has a higher product yield, and is beneficial to reducing production costs.

[0032] In some embodiments, D and E are each independently selected from a single bond or a C1-C5 alkylene group, and A, B, and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group, or a cyclic anhydride group. Preferably, when A, B, or C is substituted, the substituent is selected from a halogen, a hydrocarbon group, or a halogenated hydrocarbon group, and more preferably, when A, B, or C is substituted, the substituent is selected from a halogen, an alkyl group, or a halogenated alkyl group.

[0033] As an example, the first additive may be selected from one or more of the following compounds:

[0034] In some embodiments, D and E are each independently selected from the group shown in Structural Formula 6: Structural formula 6 Wherein, z is an integer selected from 1 to 4, R 11 and R 13 Each independently selected from a single bond or a C1-C5 alkylene group, R 12 Selected from , , , , , , , , or ; B and C are each independently selected from a substituted or unsubstituted cyclic carbonate group, a cyclic sulfate group, a cyclic sulfite group, a cyclic sulfonate group, a cyclic sulfone group, a cyclic sulfoxide group, a cyclic carboxylate group or a cyclic anhydride group. Preferably, when A, B or C is substituted, the substituent is selected from a halogen, a hydrocarbon group or a halogenated hydrocarbon group. More preferably, when A, B or C is substituted, the substituent is selected from a halogen, an alkyl group or a halogenated alkyl group.

[0035] As an example, the first additive may be selected from one or more of the following compounds: .

[0036] In some embodiments, the first additive may also be selected from one or more of the following compounds: .

[0037] It should be noted that the above are some of the compounds claimed to be protected by the present invention, but are not limited thereto and should not be construed as limiting the present invention.

[0038] A person skilled in the art who knows the structural formula of the compound of structural formula 1 can know the preparation method of the above compound according to the common knowledge in the field of chemical synthesis. For example: Compound 1-1 can be prepared by the following method: Sorbitol, dimethyl carbonate, methanol, alkaline substance catalyst potassium hydroxide and organic solvent such as DMF are placed in a reaction container, and reacted under heating conditions for several hours, and then a certain amount of oxalic acid is added to adjust the pH to neutral. After filtering and recrystallization, intermediate product 1 can be obtained. Then, intermediate product 1, carbonate, dichlorothionyl, etc. are subjected to esterification reaction under high temperature conditions to obtain intermediate product 2, and intermediate product 2 is oxidized using an oxidant such as sodium periodate to obtain compound 1-1.

[0039] Compound 1-2 can be prepared by the following method: After diacetone-D-mannitol, dimethyl carbonate, methanol, potassium carbonate and dioxane are reacted under heating and stirring for several hours, a certain amount of oxalic acid is added to adjust the pH of the solution to neutral, and the intermediate product 3 is obtained after filtering and concentration; an appropriate amount of pure water, carbonate, acid, etc. are added to the intermediate product 3 for hydrolysis reaction to obtain the intermediate product 4; then the intermediate product 4, dichlorothionyl and carbonate solvent are prepared under heating conditions to obtain the intermediate product 5; finally, the intermediate product 5 is oxidized using an oxidant such as sodium periodate to obtain compound 1-2.

[0040] In some embodiments, based on the total mass of the non-aqueous electrolyte as 100%, the amount of the first additive added is 0.01-5.0%. Specifically, the amount of the additive added can be 0.01%, 0.02%, 0.05%, 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%.

[0041] When the amount of the first additive added is too small, it cannot play a protective film-forming role and the improvement effect on battery performance is not obvious; when the amount of the first additive added is too much, the interface film formed at the negative electrode interface is too thick, which is not conducive to the shuttling of lithium ions, and the cycle performance is deteriorated. Therefore, adding an appropriate amount of the additive of structural formula 1 can improve the cycle performance of the battery.

[0042] In some embodiments, the sulfate / sulfonate compound represented by Structural Formula 2 is selected from at least one of the following compounds: .

[0043] The sulfate / sulfonate compound shown in the structural formula 2 is used as a film-forming additive, has a low oxidation potential, is easy to undergo oxidation reaction on the surface of the positive electrode material, and participates in the formation of a passivation film on the surface of the positive electrode material. The passivation film can effectively inhibit the oxidation reaction of the electrolyte solvent, and can also play a positive electrode protection role, inhibiting the dissolution of transition metals in the positive electrode material. In addition, the silicon-carbon bond in this type of compound is easily broken and combined with a trace amount of HF in the electrolyte, which plays a role in removing water and acid, and increases the content of organic components in the passivation film, increasing the toughness of the passivation film. In addition, the sulfate / sulfonate compound shown in the structural formula 2 in the additive synergizes with the first additive shown in the structural formula 1 to form a dense and stable SEI film on the negative electrode surface, effectively preventing the reduction reaction of the electrolyte on the negative electrode surface and the deposition of transition metals, improving the interface between the negative electrode and the electrolyte, and slowing down the side reactions of the electrode interface during storage or circulation, thereby improving the high temperature storage and high temperature cycle performance of the battery.

[0044] In some embodiments, the phosphate compound represented by the structural formula 3 is selected from at least one of the following compounds: .

[0045] The phosphate compound shown in the structural formula 3 acts as a positive electrode film-forming additive, and participates in the formation of a passivation film on the surface of the positive electrode material. The passivation film isolates the electrolyte from the positive electrode interface, and can inhibit the side reaction at the electrolyte and positive electrode interface, play a positive electrode protection role, and inhibit the dissolution of transition metals in the positive electrode material, improving the impedance growth and capacity loss of the battery. In addition, the phosphate shown in the structural formula 3 in the additive synergizes with the first additive shown in the structural formula 1 to form a dense and stable SEI film on the negative electrode surface, effectively preventing the reduction reaction of the electrolyte on the negative electrode surface and the deposition of transition metals, improving the interface between the negative electrode and the electrolyte, and slowing down the side reaction of the electrode interface during storage or circulation, thereby improving the high-temperature storage and high-temperature cycle performance of the battery.

[0046] In some embodiments, the amount of the first additive added is x, and the amount of the sulfate / sulfonate compound shown in Structural Formula 2 added is y, and these substances satisfy: 1%<y≤5%, and 0.01%≤x≤1%; Or 0.01%≤y≤1%, and 1%<x≤5%.

[0047] The inventors have found through research that the compound shown in Structural Formula 1 and the sulfate / sulfonate compound shown in Structural Formula 2 can be used together to improve the high-temperature storage and high-temperature cycle performance of the battery, and the ratio between the two is crucial to the improvement of battery performance. If the content of both is too low, it will not play a significant role in improving the performance of the battery. If the content of both is too high, it will cause increased gas production and affect the performance of the battery. Therefore, the total content of the compound shown in Structural Formula 1 and the sulfate / sulfonate compound shown in Structural Formula 2 must be limited to a certain range. When 1% < y ≤ 5%, and 0.01% ≤ x ≤ 1% or 0.01% ≤ y ≤ 1%, and 1% < x ≤ 5%, the battery system achieves the best high-temperature storage gas expansion and high-temperature cycle performance.

[0048] In some embodiments, the amount of the first additive added is x, and the amount of the phosphate compound shown in the structural formula 3 added is z, and these substances satisfy the following relationship: 0.1%<x+z<2%.

[0049] The compound shown in structural formula 1 and the phosphate compound shown in structural formula 3 can be used together to improve the high and low temperature storage and cycle performance of the battery, and the ratio between the two is crucial to the improvement of battery performance. If the content of both is too low, it will not play a significant role in improving the performance of the battery. If the content of both is too high, it will cause increased gas production and affect the performance of the battery. The inventor has found through research that when 0.1%<x+z<2%, the negative electrode SEI is mainly composed of the reduction product of structural formula 1, and the positive electrode SEI is mainly composed of the oxidation product of the phosphate shown in structural formula 3. At this time, the battery has a lower gas expansion rate and better high temperature storage and cycle performance.

[0050] In some embodiments, the non-aqueous electrolyte further includes a third additive, and the third additive is selected from at least one of fluoroethylene carbonate, vinylene carbonate, and a dinitrile compound.

[0051] In some embodiments, the solvent includes one or more of an ether solvent, a nitrile solvent, a carbonate solvent, and a carboxylate solvent.

[0052] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, and the cyclic ether may be, but is not limited to, one or more of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but is not limited to, one or more of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (TEGDME), and ethylene glycol dimethyl ether. The nitrile solvent may be, but is not limited to, one or more of acetonitrile, glutaronitrile, and malononitrile. Carbonate solvents include cyclic carbonates or chain carbonates. The cyclic carbonates may be, but are not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), butylene carbonate (BC), and vinylene carbonate; the chain carbonates may be, but are not limited to, one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). The carboxylate solvents may be, but are not limited to, one or more of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), butyl propionate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethyl acetate, and ethyl trimethyl acetate.

[0053] In some embodiments, the electrolyte salt is selected from lithium salts.

[0054] In a more preferred embodiment, the lithium salt is selected from at least one of LiPF6, LiPO2F2, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiDFOB, LiN(SO2CF3)2 and LiN(SO2F)2.

[0055] In some embodiments, in the non-aqueous electrolyte, the concentration of the electrolyte salt is 0.1 mol / L-8 mol / L.

[0056] In a preferred embodiment, in the non-aqueous electrolyte, the concentration of the electrolyte salt is 0.5 mol / L-4 mol / L.

[0057] Specifically, the concentration of the electrolyte salt may be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L.

[0058] Another embodiment of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, and the non-aqueous electrolyte as described above.

[0059] Since the lithium-ion battery adopts the non-aqueous electrolyte as described above, a passivation film with excellent performance can be formed on the positive electrode and the negative electrode, thereby effectively improving the cycle performance of the battery.

[0060] In some embodiments, the positive electrode includes a positive electrode active material capable of reversibly embedding / de-embedding metal lithium ions. Preferably, the positive electrode active material is selected from at least one of nickel-cobalt-manganese ternary materials, LiFePO4, LiCoO2, LiMnO2, LiNiMnO2, sulfur and their composites.

[0061] As a further preferred embodiment, the positive electrode material is LiNi x Co y M z L (1-x-y-z) O2, wherein M is selected from Mn or Al, L is Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, Cu, V or Fe; and 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤x+y+z≤1.

[0062] In some embodiments, the negative electrode includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.

[0063] In some embodiments, the battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.

[0064] The diaphragm includes a ceramic diaphragm, a rubber-coated diaphragm and a conventional diaphragm, preferably one or more of polyolefins, polyamides, polysulfones, polyphosphazenes, polyethersulfones, polyetheretherketones, polyetheramides and polyacrylonitrile. Further, it includes but is not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms. The present invention is further described below by way of examples.

[0065] Examples 1 to 50 and Comparative Examples 1 to 8 1) Preparation of electrolyte Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC = 1:1:1, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L, and then additives were added according to the tables. The amount of additives used was calculated as a percentage of the total mass of the electrolyte.

[0066] 2) Preparation of positive electrode The positive electrode active material lithium cobalt oxide LiNi was mixed in a mass ratio of 93:4:3 0.5 Co 0.2 Mn 0.3 O2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF), and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with aluminum lead wires using an ultrasonic welder to obtain a positive plate with a thickness of 120-150μm.

[0067] 3) Preparation of negative electrode The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain negative electrode slurry. The slurry is coated on both sides of the copper foil, dried, rolled and vacuum dried, and the nickel lead wire is welded with an ultrasonic welder to obtain the negative electrode plate, and the thickness of the plate is 120-150μm.

[0068] 4) Preparation of battery cells A three-layer separator with a thickness of 20 μm was placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator was wound. The wound body was flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid.

[0069] 5) Battery filling and formation In a glove box with water and oxygen contents below 20 ppm and 50 ppm respectively, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left at 45°C for 24 h.

[0070] Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 180 min, 0.1C constant current charging for 180 min, 0.2C constant current charging to 3.95 V, secondary vacuum sealing, and then further 0.2C constant current charging to 4.2 V, after being left at room temperature for 24 hours, 0.2C constant current discharge to 3.0 V.

[0071] Performance Testing (1) High temperature cycle performance test At 45°C, the formed battery is charged to 4.2V with a constant current of 1C, then charged at a constant voltage until the current drops to 0.01C, and then discharged to 3.0V with a constant current of 1C. After N cycles of charge / discharge, the capacity retention rate after the Nth cycle is calculated to evaluate its high temperature cycle performance.

[0072] The calculation formula of capacity retention rate after 45℃1C cycle N times is as follows: Nth cycle capacity retention rate (%)=(Nth cycle discharge capacity / first cycle discharge capacity)×100%.

[0073] (2) High temperature storage performance test The formed battery was charged to 4.2V at room temperature with 1C constant current and constant voltage, and the initial discharge capacity and initial battery thickness of the battery were measured. After storage at 60℃ for 30 days, the battery was discharged to 3V at 1C, and the battery retention capacity and recovery capacity as well as the battery thickness after storage were measured. The calculation formula is as follows: Battery capacity retention rate (%) = retention capacity / initial capacity × 100%; Battery capacity recovery rate (%) = recovery capacity / initial capacity × 100%; Swelling rate (%) = (battery thickness after storage - initial battery thickness) / initial battery thickness × 100%.

[0074] 1.1. The test results obtained in Examples 1 to 12 and Comparative Examples 1 to 4 are entered in Table 1.

[0075] Table 1 From the test results in Table 1, it can be seen that when 0.01-5% of the sulfate / sulfonate compound shown in Structural Formula 2 is added to the electrolyte, and the compound shown in Structural Formula 1 is used as an additive in an amount of 0.01-5%, the high temperature storage performance and high temperature cycle performance of the battery are greatly improved compared with Comparative Examples 1-4. This shows that the combination of 0.01-5% of the sulfate / sulfonate compound shown in Structural Formula 2 and 0.01-5% of the compound shown in Structural Formula 1 in the non-aqueous electrolyte can play a good role in improving the high temperature storage performance and high temperature cycle performance of the battery in a large range. It can be seen from Comparative Example 3 that when the mass percentage of the compound shown in Structural Formula 1 is greater than 5%, even if the two are used together, the high temperature storage and high temperature cycle performance of the battery cannot be significantly improved.

[0076] 1.2. The test results obtained in Examples 2 to 6, 13, 14 and Comparative Examples 1 and 2 are entered in Table 2.

[0077] Table 2 It can be seen from the test results in Table 2 that in Examples 2 to 6, the addition amount (x) of the compound represented by Structural Formula 1 satisfies 1.0%<x≤5.0%, and the addition amount (y) of the sulfate / sulfonate compound represented by Structural Formula 2 satisfies 0.01%≤y≤1%. Although the addition amount of the sulfate / sulfonate compound represented by Structural Formula 2 in Example 13 is also within the range of 0.01%≤y≤1%, the addition amount of Structural Formula 1 is only 0.9%. The test results show that the capacity retention rate of high-temperature cycles is lower than that of Examples 2 to 6, and the capacity retention rate and capacity recovery rate of high-temperature storage are both more than 5 percentage points lower than those of Examples 2 to 6, and the inflation rate is more than 5 percentage points higher than that of Examples 2 to 6.

[0078] Similarly, although the addition amount of the compound shown in structural formula 1 of Example 14 is also within the range of 1.0%<x≤5.0%, the addition amount of the sulfate / sulfonate compound shown in structural formula 2 is 1.1%. The test results show that its capacity retention rate of high temperature cycle is lower than that of Examples 2 to 6 on average, and the capacity retention rate and capacity recovery rate of high temperature storage are both more than 3 percentage points lower than those of Examples 2 to 6, and the inflation rate is about 5 percentage points higher than that of Examples 2 to 6.

[0079] It shows that when the addition amount (y) of the sulfate / sulfonate compound shown in Structural Formula 2 satisfies 0.01%≤y≤1%, and the addition amount (x) of the compound shown in Structural Formula 1 satisfies 1.0%<x≤5.0%, it plays a significant role in improving the high-temperature storage and high-temperature cycle performance of the battery.

[0080] 1.3. The test results obtained in Examples 7 to 12, 15, 16 and Comparative Examples 1 and 2 are entered in Table 3.

[0081] Table 3 It can be seen from the test results in Table 3 that in Examples 7 to 12, the addition amount (x) of the compound represented by Structural Formula 1 satisfies 0.01%≤x≤1.0%, and the addition amount of the sulfate / sulfonate compound represented by Structural Formula 2 satisfies 1.0%<y≤5.0%. Although the addition amount of the sulfate / sulfonate compound represented by Structural Formula 2 of Example 15 is also within the range of 1.0%<y≤5.0%, the addition amount of Structural Formula 1 is 1.1%. The test results show that its high temperature capacity retention rate is on average more than 5 percentage points lower than that of Examples 7 to 12.

[0082] Similarly, although the addition amount of the compound represented by structural formula 1 of Example 16 is also within the range of 0.01%≤x≤1.0%, the addition amount of the sulfate / sulfonate compound represented by structural formula 2 is only 0.9%. The test results show that its capacity retention rate of high-temperature cycle and high-temperature storage is about 5 percentage points lower than that of Examples 7 to 12, while the inflation rate of high-temperature storage is more than doubled that of Examples 7 to 12.

[0083] It shows that when the addition amount (y) of the sulfate / sulfonate compound shown in Structural Formula 2 satisfies 1.0%<y≤5.0%, and the addition amount (x) of the compound shown in Structural Formula 1 satisfies 0.01%≤x≤1.0%, it plays a significant role in improving the high-temperature storage and high-temperature cycle performance of the battery.

[0084] 1.4. The test results obtained in Examples 17 to 27 and Comparative Examples 1 and 2 are entered in Table 4.

[0085] Table 4 It can be seen from the test results in Table 4 that when the addition amount (y) of the sulfate / sulfonate compound shown in Structural Formula 2 satisfies 1.0%<y≤5.0%, and the addition amount (x) of the compound shown in Structural Formula 1 satisfies 0.01%≤x≤1.0%, or 0.01%≤y≤1%, and 1.0%<x≤5.0%, the high temperature storage and high temperature cycle performance of the battery are improved to varying degrees by adding different compounds shown in Structural Formula 1 to the electrolyte.

[0086] 1.5. The test results obtained in Examples 28 to 33 and Comparative Examples 5 to 8 are entered in Table 5.

[0087] Table 5 It can be seen from the test results in Table 5 that the electrolyte in the embodiment is added with 0.01-1.0% of the phosphate compound shown in structural formula 3, and the compound shown in structural formula 1 is used as the first additive in an amount of 0.01-5%. The high temperature storage and cycle performance of the battery are greatly improved compared with those of comparative examples 5-8.

[0088] It can be seen from Comparative Example 5 that when the compound shown in Structural Formula 1 is not added, the negative electrode SEI is composed of the reduction product of the phosphate compound shown in Structural Formula 3, which has a large negative electrode impedance. Moreover, due to the large consumption of phosphate at the negative electrode and insufficient protection of the positive electrode, the positive electrode stability of the battery is poor, and the high-temperature storage and high-temperature cycle performances are deteriorated.

[0089] It can be seen from Comparative Example 6 that when the phosphate compound shown in Structural Formula 3 is not added, the high-temperature storage and high-temperature cycle performances are insufficient. This is because there is no phosphate to passivate the positive electrode, resulting in continuous decomposition of the electrolyte at the positive electrode interface under high-temperature fully charged state.

[0090] It can be seen from Comparative Example 7 that when the content of the compound represented by Structural Formula 1 is greater than 5%, due to the increase in the negative electrode film formation resistance, even if the phosphate compound represented by Structural Formula 3 is added, the high temperature performance cannot be significantly improved.

[0091] It can be seen from Comparative Example 8 that when the content of the compound represented by Structural Formula 3 is greater than 1%, the negative electrode impedance is relatively large, and even if the compound represented by Structural Formula 1 is added, the high-temperature performance cannot be significantly improved.

[0092] This indicates that adding the phosphate compound represented by structural formula 3 in combination with 0.01 to 5% of the compound represented by structural formula 1 in the non-aqueous electrolyte can improve the high-temperature storage and cycle performance of the battery over a large range.

[0093] 1.6. The test results obtained from Examples 34 to 38 and Comparative Examples 5 to 6 are entered in Table 6.

[0094] Table 6 From the test results in Table 6, it can be seen that in Examples 34 to 38, the addition amount (x) of the compound shown in Structural Formula 1 is in the range of 0.01 to 5%, and the addition amount (z) of the phosphate compound shown in Structural Formula 3 is also in the range of 0.01 to 1.0%. However, only Examples 34 to 36 satisfy 0.1% < x + y < 2%. In Example 37, the content of the compound shown in Structural Formula 1 and the phosphate shown in Structural Formula 3 is too small, and the total addition amount of the two is only 0.09%. The positive and negative electrode protection effects are weak, so the high-temperature storage and high-temperature cycle performance are poor. In Example 38, the content of the compound shown in Structural Formula 1 and the phosphate shown in Structural Formula 3 is too much, and the total addition amount of the two reaches 3.0%. At this time, the electrolyte-electrode interface impedance is too large, resulting in a huge overpotential and deteriorating the cycle performance, and the high-temperature storage performance is also deteriorated due to the oxidation and decomposition of the additive itself. Therefore, the sum of the added amounts of the compound of structural formula 1 and the phosphate ester shown in structural formula 3 needs to meet certain conditions to achieve better comprehensive performance. It can be seen that when 0.1%<x+y<2%, the battery has better comprehensive performance. 1.7. The test results obtained from Examples 39-50 and Comparative Examples 5-6 are entered in Table 7.

[0095] Table 7 It can be seen from the test results in Table 7 that when the addition amount (x) of the compound represented by Structural Formula 1 is in the range of 0.01 to 5%, the addition amount (z) of the phosphate compound represented by Structural Formula 3-3 is also in the range of 0.01 to 1.0%. By adding different compounds represented by Structural Formula 1 to the electrolyte, the high-temperature cycle and high-temperature storage performance of the battery are improved to varying degrees.

[0096] In summary, the present invention can significantly improve the high temperature storage and high temperature cycle performance of the battery by adding the compound shown in structural formula 1 to the non-aqueous electrolyte and using it in combination with the sulfate / sulfonate compound shown in structural formula 2 or the phosphate compound shown in structural formula 3. The inventors have found through a large number of experiments that the improvement of battery performance is related to the ratio and content of the first additive and the second additive. Further research has found that when the second additive is a sulfate / sulfonate compound shown in structural formula 2, the mass percentage (x) of the compound shown in structural formula 1 and the mass percentage (y) of the sulfate / sulfonate compound shown in structural formula 2 meet 0.01%≤x≤1.0%, and 1.0%<y≤5.0%, or 1.0%<x≤5.0%, and 0.01%≤y≤1%, the comprehensive performance of the battery is significantly improved. When the second additive is a phosphate compound shown in Structural Formula 3, the mass percentage (x) of the compound shown in Structural Formula 1 and the mass percentage (z) of the phosphate compound shown in Structural Formula 3 satisfy 0.01%<x≤5%, 0.01%<z≤1%, and 0.1%<x+z<2%, the overall performance of the battery is significantly improved.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that: The invention comprises a solvent, an electrolyte salt, a first additive and a second additive, wherein the electrolyte salt is selected from a lithium salt, wherein the lithium salt is selected from at least one of LiPF6, LiPO2F2, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiDFOB, LiN(SO2CF3)2 and LiN(SO2F)2, and the first additive is selected from at least one of the following compounds: ; The second additive is selected from sulfate / sulfonate compounds, and the sulfate / sulfonate compounds are selected from at least one of the following compounds: ; Based on the total mass of the non-aqueous electrolyte as 100%, the amount of the first additive added is 0.01-5.0%; The added amount of the sulfate / sulfonate compound is 0.01-5.0%.

2. The non-aqueous electrolyte according to claim 1, characterized in that Taking the total mass of the non-aqueous electrolyte as 100%, the amount of the first additive added is x, and the amount of the sulfate / sulfonate compound added is y, then these substances satisfy the following conditions: 1%<y≤5%, and 0.01%≤x≤1%; Or 0.01%≤y≤1%, and 1%<x≤5%.

3. The non-aqueous electrolyte according to claim 1, characterized in that: The non-aqueous electrolyte further includes a third additive, and the third additive is selected from at least one of fluoroethylene carbonate, vinylene carbonate, and a dinitrile compound.

4. The non-aqueous electrolyte according to claim 1, characterized in that: The concentration of the electrolyte salt is 0.1 mol / L-8 mol / L.

5. The non-aqueous electrolyte according to claim 4, characterized in that It is characterized in that The concentration of the electrolyte salt is 0.4 mol / L-4 mol / L.

6. The non-aqueous electrolyte according to claim 1, characterized in that: The solvent includes one or more of an ether solvent, a nitrile solvent, a carbonate solvent and a carboxylate solvent.

7. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte according to any one of claims 1 to 6.

8. The lithium-ion battery according to claim 7, characterized in that: The positive electrode includes a positive electrode active material capable of reversibly inserting / deinserting metal lithium ions, and the positive electrode active material is selected from at least one of nickel-cobalt-manganese ternary materials, LiFePO4, LiCoO2, LiMnO2, LiNiMnO2, sulfur and a composite thereof.

9. The lithium-ion battery according to claim 8, characterized in that: The positive electrode active material is LiNi x Co y M z L (1-x-y-z) O2, wherein M is selected from Mn or Al, L is Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, Cu, V or Fe; and 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤x+y+z≤1.